2019
DOI: 10.1002/asia.201801779
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of 3‐Deoxy‐dmanno‐oct‐2‐ulosonic Acid (Kdo) Glycosides Containing α‐(2→4)‐Linked Kdo‐Kdo Unit

Abstract: Ac onvenient and divergenta pproach was developed to prepare diverse bacterial 3-deoxy-d-manno-oct-2ulosonic acid (Kdo) oligosaccharides containing aK do-a-(2!4)-Kdo fragment. The orthogonal protected a-(2!4) linked Kdo-Kdo disaccharide 3,s erving as ac ommon precursor,w as divergently transformed into the corresponding 8-, 8'-, and4 '-hydroxy disaccharides 5, 7,a nd 14,r espectively.Then, these alcohols were glycosylated, respectively,w ith the 5,7-O-di-tert-butylsilylene (DTBS) protected Kdo thioglycoside do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These disaccharides are orthogonally substituted. The C4, C5′/7′, and C8′ positions of 5 were protected, respectively, by an allyl (All) ether, a cyclic DTBS acetal, and a tert ‐butyldimethylsilyl (TBS) ether, [22] while the C4 and C4′ positions of 6 were substituted, respectively, by an All and a TBS group. So, the use of these orthogonal protecting groups will make it possible to install Kdo or Glc p NA moieties at C4‐, C4′‐, or C5′‐branching points in an optimal order, thus leading to the expected backbones.…”
Section: Resultsmentioning
confidence: 99%
“…These disaccharides are orthogonally substituted. The C4, C5′/7′, and C8′ positions of 5 were protected, respectively, by an allyl (All) ether, a cyclic DTBS acetal, and a tert ‐butyldimethylsilyl (TBS) ether, [22] while the C4 and C4′ positions of 6 were substituted, respectively, by an All and a TBS group. So, the use of these orthogonal protecting groups will make it possible to install Kdo or Glc p NA moieties at C4‐, C4′‐, or C5′‐branching points in an optimal order, thus leading to the expected backbones.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Huang et al. reported that Kdo ethyl thioglycosides with C5‐OH and C7‐OH as TBS ethers were highly effective donors for the stereoselective synthesis of α‐Kdo glycosides [26,27] . Initially, the role of cyclic acetals in stereoselectivity was evaluated by different types of donors with and without a cyclic protecting group.…”
Section: Synthesis Of α‐Kdo Glycosidesmentioning
confidence: 99%
“…[18b-c,20a-b,25] In 2015, Huang et al reported that Kdo ethyl thioglycosides with C5-OH and C7-OH as TBS ethers were highly effective donors for the stereoselective synthesis of α-Kdo glycosides. [26,27] Initially, the role of cyclic acetals in stereoselectivity was evaluated by different types of donors with and without a cyclic protecting group. After the ideal conditions for αselectivity were established, a range of acceptors was used to produce α-Kdo glycosides (Scheme 3).…”
Section: Glycosylation Of 57-o-di-tert-butylsilylene (Dtbs) Protected...mentioning
confidence: 99%
“…The α-configuration of the newly formed fucoside was unambiguously confirmed by the characteristic doublet for the anomeric signal of the α- l -Fuc p moiety (δ H1′ 5.29, d, J H1′/H2′ = 3.4 Hz). Then, the TBS group of 11 was selectively removed with 20 equiv of Et 3 N·3HF to clearly furnish the corresponding disaccharide alcohol 12 . Condensation of this compound with 4,6- O -benzylidene-protected d -thiogalactoside donor 7 under similar activation conditions as described above gave exclusively α-(1→3)-linked trisaccharide 13 in a good 73% yield.…”
mentioning
confidence: 99%